Hello! The answer to your question would be as followed:
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
-79-(7*w+3*(4*w-1)=0
-79 - (7w + 3 • (4w - 1)) = 0
Pulling out like terms :
Pull out like factors :
-19w - 76 = -19 • (w + 4)
-19 • (w + 4) = 0
Equations which are never true :
Solve : -19 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation :
Solve : w+4 = 0
Subtract 4 from both sides of the equation :
w = -4
w = -4